A Dual‐Functional Graphene‐Based Self‐Alarm Health‐Monitoring E‐Skin. (14th October 2019) - Chen, Xianping; Luo, Feng; Yuan, Min; Xie, Dingli; Shen, Li; Zheng, Kai; Wang, Zeping; Li, Xiandong; Tao, Lu‐Qi
Abstract: Diseases such as cardiovascular problems and sleep apnea cause mass deaths annually due to a lack of timely and portable monitoring and alarm measures. Various wearable devices for health monitoring have been intensely researched to reduce mortality. However, these devices themselves can only detect physiological signals; they cannot sound an alarm. Therefore, they must rely on mobile phones or other peripheral devices such as speakers or vibration motors to sound an alarm, which may result in a patient missing the optimal treatment. It is valuable to develop a self‐alarm health monitoring device with the dual functions of physiological signal detection and sound alarm simultaneously. A one‐step laser‐induced graphene (LIG)‐based electronic skin (E‐skin) is fabricated to perform health monitoring and alarm at the same time, which benefit from its both excellent mechanical and acoustical performance. These customized shutter‐patterned E‐skins have an ultrahigh sensitivity of 316.3 and can detect various biosignals such as wrist pulse, respiratory, etc. They also have a self‐alarm function and can sound an alarm when detecting abnormal situations. This study addresses the multifunctional integration required for multisensors, which will open further applications in wearable sensors and health‐care devices. Abstract : The development of E‐skin with dual functionality, integrating strain detection and alarm into a single device, is crucial for health monitoring. A one‐step laser‐induced graphene (LIG)‐based E‐skin that can detect faint biosignals (respiration, pulse, etc.) and issue thermoacoustic sound to warn when detecting some abnormal conditions (sleep apnea, sudden cardiac arrest).